Foetal Development in Mammals (International Journal of Medical and Surgical Sciences, 2014)
During the fetal period are carried out a series of necessary changes, which prepare the fetus for extrauterine life, culminating embryonic development, leading to this physiological maturation of tissues, organs and systems, along with a rapidly growing body. Well being bought, the species-specific features. Other events of interest are beginning the process of ossification of the bones (short and long), formation of the eyelids; integumentary and other elements besides the surfactant secretion from lungs. In this paper we will make a description of the main events that characterized this period, along with a comparison of them among some domestic mammals.
Keywords: Foetus; Mammal; Bovine; Ovine; Feline; Maturing